Designing a persuasive physical activity application for older workers: Understanding end- user perceptions - Mohd Mohadis, Hazwani; Mohamad Ali, Nazlena; Smeaton, Alan F. (Taylor and Francis, 2016)
Among the factors known to encourage healthy ageing is routine physical activity, a behaviour that is not common among the older age group. A Persuasive System Design (PSD) model offers guidelines for designing and evaluating systems aimed at reinforcing, changing or shaping underlying human behaviour and attitudes. The objective of this study was to investigate the perceptions of older workers towards persuasive principles of PSD that was integrated into an application specifically designed to encourage physical activity. Ten older workers aged 50–64 years with different physical activity levels participated in this study. Using a think-aloud technique, the participants interacted with a physical activity application, while verbally expressing their perceptions towards the persuasive elements. The results indicated that the older worker participants had positive views towards persuasive design principles that fell under the categories of primary task, dialogue support and credibility support. However, the persuasive principle of the social support category received contradictory views. Further, it was discovered that the personalisation of persuasive principles, the credibility of tailored contents and the establishment of a sense of similarity are imperative in the designing of effective persuasive physical activity applications targeting older workers.